Sensitive and selective chemiluminescence assay for hydrogen peroxide in exhaled breath condensate using nanoparticle-based catalysis - Li, Xiaohua; Zhang, Zhujun; Tao, Liang; Gao, Miao (Spectrochimica acta. Part A, Molecular and biomolecular spectroscopy, 2013)
[Display omitted] ► Nanoparticles were studied using both microarray method and FI-CL method. ► Nanoparticles exhibit high specific catalytic effects on luminol–H2O2 system. ► A reaction mechanism was disscussed. ► It provides new insights into the application of nanoparticle materials. ► A novel method for H2O2 determination exhaled breath condensate (EBC) is reported. The catalytic properties of cubiform Co3O4 nanoparticles, α-Fe2O3 nanorods, and NiO nanoparticles were studied using both microarray method and FI-CL method. These nanoarticles exhibit high specific catalytic effects on the chemiluminescence (CL) reaction of the luminol–H2O2 system in alkaline solution compared with other common catalysts. A reaction mechanism is described. It provides new insights into the application of nanoparticle materials. The CL method based on the use of the Co3O4 nanoparticles is ultrasensitive and particularly selective. Therefore, it was applied to the analysis of H2O2 which can be determined in the concentration range from 1.0nM to 1000nM, with a detection limit of 0.3nM. The relative standard deviation is 2.1% at 0.1μM of H2O2 (for n=11). The method was successfully applied to the determination of trace quantities of H2O2 in exhaled breath condensate (EBC) where it is a mediator of oxidative stress and a promising biomarker for diagnosing. The assay requires a small sample and no incubation time, and has an analytical runtime of <1min. It is timesaving and suitable for larger studies. The levels of H2O2 in EBC are found to be elevated in healthy subjects (average=0.54nM), rheum subjects (average=0.24nM), and feverish subjects (average=0.16nM). Our data suggested that the average H2O2 concentration of EBC from feverish subjects was significantly higher than healthy subjects and rheumatic subjects.